Subtilisin-like proteases and lipid signalling events play an important role in grapevine resistance to downy mildew: a systems biology approach - Figueiredo, Andreia (2019)
The reduction of pesticide use to control pests and diseases is one of modern agriculture’s demands. In the grapevine-Plasmopara viticola pathosystem, repeated preventive applications of fungicides occur during the vegetative period. The identification of specific mechanisms or molecules with bioactive fungicide properties may lead to new disease control strategies. Following an omics-based system biology approach we were able to identify both subtilisin-like proteases and lipid associated signalling events as key players on grapevine resistance mechanisms. Efforts are being conducted to characterize their role aiming at the definition of alternative control measures towards a sustainable viticulture.